Structure and Constraints on Community Newspaper Gatekeepers - Richard Carlson (Journal of Applied Communications, 1990)
A review of "Structure and Constraints on Community Newspaper Gatekeepers," by G.A. Donohue, C.N Ollen and P.J. Tichenor.